Factors Affecting Medication Dispensing and Counselling Practices in Hospital Pharmacy Settings in Northwest Nigeria (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Medication dispensing and counselling are routine but very important activities carried out by pharmacists in a wide variety of healthcare settings. While these processes are often overlooked when issues around the rational use of medication are being considered, any mistake(s) in one or both processes can seriously undermine patient care.Objective: To assess selected factors, and identify problems affecting medication dispensing and counselling in outpatient hospital pharmacies in northwest Nigeria.Methods: Mixed methods were used to collect data from 19 outpatient pharmacies in eight public hospitals located in Kaduna and Kano states from November 2019 to March 2020. Quantitative data was generated from a survey, while qualitative data was collected from key-informant interviews with heads of the pharmacies. Data collected from the survey were analyzed to generate descriptive statistics (frequencies and percentages), while interview data were transcribed and analyzed using thematic/content analysis.Results: Only two pharmacies (10.5%) had dispensing standard operating procedures, and only one (5.2%) had a completely private counselling area. Pharmacy technicians were present in most of the pharmacies (84.2%), and students were widely involved in medication dispensing and counselling activities (73.7%). Identified problems from the interviews included issues with prescribers and medication availability, inadequate staffing levels and absence of materials and/equipment required for dispensing and counselling.Conclusion: There is an urgent need for multi-faceted interventions to improve on several of these findings and enhance the quality of care provided to patients.